PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN KETERAMPILAN BERBICARA MAHASISWA DI ORGANISASI AN-NADI UIN MATARAM. - Jalaluddin Jalaluddin; Agus Yasin; Moh. Nasikin; Afin Al Aufi (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This study aims to examine the use of audiovisual media in teaching speaking skills to students involved in the An-Nadi organization at the State Islamic University of Mataram. The primary focus of this research is to describe the use of audiovisual media and identify the obstacles and solutions related to the teaching of speaking skills. A qualitative approach was employed to gather data that reflects the real situation in the field, using observation, interviews, and documentation techniques. Data analysis was conducted using qualitative descriptive methods through three stages: data reduction, data presentation, and data verification. The validity of the data was tested through persistent observation, sufficient references, and triangulation. The results of the study indicate that the use of audiovisual media in teaching speaking skills within the An-Nadi organization involves activities such as watching, practicing, and explaining short Arabic-language videos or films. The obstacles identified include student conditions, limited media resources, and a lack of qualified instructors. Proposed solutions include allocating organizational funds, improving organizational discipline, raising individual awareness, and strengthening organizational consciousness.